Chinese cross-border acquisitions in developed economies : the organization of knowledge transfer and the impact on business-to-business customer and supplier relationships of the acquired enterprise - Haasis, Timon Immanuel; Justus Liebig University Giessen (My University, 2018)
This dissertation addresses two research gaps in the literature on Chinese cross-border acquisitions (CBAs) in developed economies (DEs). On the one hand, it examines how knowledge transfer (KT) in the context of Chinese CBAs in DEs is organized on the firm level from an organizational learning perspective. On the other hand, against the background of a rising importance of company networks due to the emergence of the knowledge-based economy, it investigates the impact of Chinese CBAs on the existing business-to-business (B2B) customer and supplier relationships of the acquired enterprise.Empirically, this thesis employs a multiple case study and investigates Chinese acquisitions in the German industrial sector as a representative sample of Chinese CBAs in DEs. In addition, this thesis carries out a systematic review of the academic literature on the internationalization of Chinese firms (ICF) published between 2011 and June 2017, supplementing a previous review article on this subject by Deng (2012) and ensuring that the empirical investigation is based on the most recent research results.The findings of this dissertation reveal that the management actions to achieve KT in the context of Chinese CBAs in DEs include the establishment of jointly operated R&D centers and joint ventures, as well as the reaching of license agreements between the Chinese parent company and the acquired target firm. Additional management measures include the training of employees, the formation of international project teams, the ue of digital communication tools, and the posting of employees abroad.Another central finding of this thesis is that while the dominant KT direction remains from the acquired enterprise to the Chinese parent company and knowledge transmission in particular concerns the technological area, KT meanwhile also occurs bi-directionally.The effectiveness of the KT process is moderated by the absorptive and disseminative capacities of the employees of the Chinese parent company and the acquired firm, knowledge characteristics, and the handling of intercultural issues.Furthermore, the research results of this dissertation demonstrate that Chinese CBAs in DEs hardly lead to significant and permanent adverse effects on the existing B2B customer and supplier network of the acquired enterprises from DEs. The rather preserving integration behavior of Chinese acquirers, the long-term strategic orientation of the Chinese parent com-panies and the involvement of key customers during the negotiation phase explain this result.
Keywords: ddc:910